The effect of gamma-somer of benzene hexachloride upon the microflora of submerged rice soils. II. II. Effect upon nitrogen mineralization and fixation, and selected bacteria - Raghu, K.; MacRae, I.C. (Canadian Science Publishing, 1967)
The effect of applications of γ-benzene hexachloride (γ-BHC) to two submerged tropical soils at rates equivalent to recommended field practice (5 kg/ha) and 10 times this level upon the mineralization of native soil nitrogen was studied. No inhibitory effect on nitrogen mineralization was detected. A significant increase in the amount of nitrogen mineralized was detected in one of the soils over a period of 16 weeks of submergence. Additions of γ-BHC at 6 kg/ha resulted in significant increases in nitrogen fixation in both soils. Populations of anaerobic, phosphate-dissolving bacteria were found to be higher in the two soils when they were treated with γ-BHC at 6 kg/ha.